Examining the judicial decision to substitute credibility instructions for expert testimony on confessions. (13th September 2014) - Gomes, Dayna M.; Stenstrom, Douglas M.; Calvillo, Dustin P.
Abstract : Purpose: The present study tested the judicial decision to deny false confession expert testimony on the basis that jury instructions are sufficient to aid jurors in their determinations of disputed confession evidence. Methods: Three groups of mock jurors ( N = 150) were presented with a trial summary that included a videotaped re‐enactment of an interrogation in which the interrogator used a maximization ploy. One group received expert testimony in the trial summary, another group received credibility instructions, and a control group received neither. All participants received standard reasonable doubt instructions at the end of the trial summary and then answered questions such as their verdict in the case, the defendant's likelihood of guilt, and the voluntariness of the defendant's confession. Results: The results showed a high rate of conviction that was only reduced when participants received expert testimony. Across all measures, no significant differences were found between the control and credibility instruction groups. Conclusions: The results suggest that credibility instructions are not comparable to expert testimony in influencing jurors' judgments of disputed confession evidence. These findings do not support the judicial decision to deny expert testimony on the basis that credibility instructions alone are sufficient to aid potential jurors in their evaluations of confession evidence. Avenues for future research on expert testimony and jury instructions in confession cases are discussed.